Conceptual Utility Model for the Management of Stress and Psychological Wellbeing, CMMSPW™ in a university environment: theoretical basis, structure and functionality - de la Fuente, Jesús; Martínez-Vicente, José Manuel (Frontiers in Psychology, 2024)
This article describes and introduces the Conceptual Utility Model for the Management of Stress and Psychological Wellbeing, CMMSPW TM Its purpose is to assess, evaluate and treat stress and psychological wellbeing. First, the theoretical assumptions of the model are presented. This Model is an application of the 3P Model, Theory of Internal vs External Behavioral Regulation and the Model of Competency for the Management of Stress and Psychological Wellbeing. Second, the conceptual structure of the model is presented. This model allows the structural and functional determination of the variables and predictive, mediating and final factors for stress and psychological wellbeing. Third, the functional structure is presented. For predictive factors, the internal and external self-regulation theoretical model allows us to assess levels of internal and external regulation of the individual and their context, as well as other personal and contextual factors involved in self-regulation. For mediating factors, the model of competence for the management of stress and wellbeing allows us to analyze conceptual (concept and principles). mediating (skills and metaskills) and attitudinal (attitudes, values and habits) variables. Finally, in relation to factors that condition outcomes, we can determine levels of response to stress and psychological wellbeing. Finally, limitations and conclusions are presented. The model also allows us to determine predictive relationships between those three types of variables and is functionally transferable to other contexts, including contexts proper to the psychology of education, clinical practice and healthcare, and psychosocial, organizational and technological contexts.